HUBUNGAN ANTARA SIKAP DENGAN PRAKTIK PENYULUHAN TENTANG ASI EKSKLUSIF KADER KESEHATAN DESA SIAGA AKTIF - Titi Mursiti; Sri Setiasih; Ana Sundari (Midwifery Care Journal, 2020)
Death in newborn can be prevented by breast feeding. Infants who are breastfed early will begin their lives in the healthiest way. The prelimenary survey was conducted on 10 active health cadres in Peron Village and Kedungboto Village, 6 of whom had less supportive attitudes towards exclusive breeastfeeding.The purpose of this study was determine the relationship between attitudes and exclusive breastfeeding practice in active village health cadres.This type of research is observational analytic, which is descriptive quantitative by using a cross sectional approach. The data source is primary data and secondary data. The Sample of this study is the total population, a total of 50 respondents.The results showed that attitudes abouit exclusive breastfeeding was classified as a good with a score of 6-8 by 68% (34 people).There is asignificant relationship between attitudes with the practice of exclusive breastfeeding counseling for active villages health cadres, advice for policy makers to develop programs for seminars or training on exclusive breastfeeding for health cadres of in active alert villages.